Effect of screw cleaner on cotton spinning - Tuychiev T, Tuychiev T; Turdiev H, Turdiev H; Rozmetov R, Rozmetov R; Shorakhmedova M, Shorakhmedova M (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article presents the results of research carried out in production conditions to determine the effect of the 6A-12M1 small dirt cleaning equipment on cotton fiber fluffing and the effect of these blown cotton fibers on the change in the amount of fluffed cotton pieces when processed in the UXK small and large dirt cleaning equipment. According to the results of the research, 28.22% of the fibers of cotton pieces were blown in the 6A-12M1 cleaner, while the amount of blown cotton pieces was reduced to 11.46%, and the amount of unblown cotton was reduced to 88.54% when cleaning large impurities in the 2 saw drums and colosnic modules located in the UXK cleaning complex. So, it was found that in the presence of 2 sawing drums and a colosnik gid module in the UXK cleaning complex, it is possible to reduce the amount of cotton particles by up to 2.5 times when cleaning large impurities.